PENGGUNAAN MEDIA SOSIAL INSTAGRAM UNTUK MENGEMBANGKAN KEMATANGAN KARIR PESERTA DIDIK KELAS XII DI SEKOLAH MENENGAH ATAS - Lani Cahyani; Herdi Herdi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The research aims to find out the use of Instagram social media to increase the career maturity of grade XII students in Senior High School. This study uses the method A mix of interviews and questionnaires distributed through google forms and analyzed using descriptive statistics. The result of this study is that Instagram social media deserves to be a medium used by counseling guidance teachers in organizing career guidance because it can help students to explore their careers. Based on the usefulness, ease of access, and attractiveness of career information presented through the isntagram media, all aspects received a very good response, shown by a percentage of > 70%.